A CoII complex for 19F MRI-based detection of reactive oxygen species. Issue 96 (14th November 2016) - Yu, Meng; Xie, Da; Phan, Khanh P.; Enriquez, José S.; Luci, Jeffrey J.; Que, Emily L.
Abstract : A fluorinated, cobalt(ii )-based 19 F MRI imaging agent switches from a paramagnetic high spin Co II state to a diamagnetic low spin Co III state following oxidation by H2 O2 and other reactive oxygen species, resulting in a turn-on response via both 19 F NMR and MRI. Abstract : A fluorinated, air-stable cobalt(ii ) complex serves as a turn-on 19 F magnetic resonance imaging (MRI) tracer for reactive oxygen species including H2 O2 . Upon oxidation with H2 O2, the complex converts from paramagnetic high spin Co II to diamagnetic low spin Co III resulting in a chemical shift change and enhancement in 19 F NMR signal. Further, the oxidation can be reversed in the presence of reductant Na2 S2 O4 . The turn-on response is demonstrated by 19 F MRI, characterized by a ∼2–3 fold enhancement in signal.